Rechargeable Sodium-Ion Battery Based on a Cathode of Copper Hexacyanoferrate - Herrera-Diaz, F; Herrera-Diaz, F (Springer Science and Business Media Deutschland GmbH, 2023)
In this work, the performance of copper (II) hexacyanoferrate(III) (CuHCF) as a cathode material for sodium-ion batteries was studied. The compound was synthesized by a precipitation reaction in aqueous solution in a closed system. The morphology and structure show nanoparticles agglomerated with sizes ranging between 40 and 70 nm and a crystalline phase with a cubic structure, respectively. The material exhibited a stable performance with a working potential of around 3.4 V vs. Na+/Na. The gravimetric capacity obtained is close to 30 mAh g−1 for 100 cycles at a rate of C/20, which is around half of the capacity for CuHCF when it encounters water in its structure, e.g., zeolite-type (60 mAh g−1), which is less than the theoretical capacity for this material (85.1 mAh g−1). CuHCF could be a promising cathode material for sodium-ion batteries considering its electrochemical performance. © 2023, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.